The orchard - Lewis, Beverly, 1949- (Bethany House, a division of Baker Publishing Group, 2022)
"For generations, Ellie Hostetler's family has tended their orchard, a tradition her twin brother, Evan, will someday continue. But when Evan is drafted for the Vietnam War, the family is shocked to learn he has not sought conscientious objector status. Ellie, with the support of a new beau, will need to find the courage to face a future unlike the one she imagined."